Emotional competence: how can games contribute to their development (Research, Society and Development, 2020)
Many experiences influence or develop emotional skills, among which we highlight the interaction with games. This work aims to discuss the games and how they can influence the development of emotional skills, trying to describe what to reveal or the game as an alternative to create experiences that help, especially children, to deal with their emotions. To this end, a narrative literature review was conducted, observing procedures such as the survey of theoretical references that describe the concepts related to the problem in question, a definition of central references, reading, and systematization of these references, analysis, and discussion. The review enlightened that emotional competence involves how we express and deal with emotions and that competence can be improved. The results reinforce the games, as activities that involve rules, challenges, objectives, and consequences, can contribute to its development. It is concluded that intentional activities based on the use of games and mediation can offer significant contributions in contexts of school intervention.